MONITORING DAN EVALUASI STRATEGI DAN RENCANA AKSI KONSERVASI (SRAK) ORANGUTAN INDONESIA 2008-2014 UNTUK ORANGUTAN SUMATERA (Pongo abelii) - Akhirul Hijry; Pindi Patana; Rahmawaty Rahmawaty (Program studi Kehutanan USU, 2016)
Determination of the Strategy and Action Plan (SRAK) Orangutan Indonesian Conservation 2007-2017 is a useful framework that combines the handling of priority conservation , integration , and involvement all parties and stakeholders in Sumatran orangutans (Pongo abelii) conservation). The aims of this study is to evaluate the implementation and achievement of SRAK from 2008 to 2014 for Sumatran orangutan (Pongo abelii). This research was conducted by using a Likert scale method to evaluate the achievement of the program and the Force Field Analysis method to determine the ‘driving force’ and the ‘restraining force’ of the action program. The results showed that SRAK for Sumatran Orangutan (Pongo abelii) 2008-2014 achieved 65 % of program, but not for all indicators. Keywords: Conservation Action, Monitoring and Evaluation, Orang Utan Sumatera (Pongo abelii)